The metabolic landscape of ovarian cancer stem cells: how do they survive? - Tan, Jixue; Tang, Lin; Zhang, Qian (Frontiers in Oncology, 2026)
Ovarian cancer remains one of the most lethal malignancies of the female reproductive system, with its high mortality rate largely driven by chemotherapy resistance and disease recurrence. Ovarian cancer stem cells (OCSCs), a small subpopulation within ovarian tumors, are characterized by their capacity for self-renewal, differentiation, and tumorigenic growth. They are recognized as central drivers of tumor initiation, metastasis, drug resistance, and relapse. Mounting evidence in recent years has highlighted the pivotal role of metabolic reprogramming in sustaining OCSC stemness and therapeutic resistance. In this review, we reported the major metabolic pathways engaged by cancer stem cells (CSCs), including glucose metabolism (glycolysis, the tricarboxylic acid cycle, oxidative phosphorylation, and reactive oxygen species regulation), lipid metabolism, and amino acid metabolism. These pathways function to meet the bioenergetic and biosynthetic requirements of CSCs. Particular emphasis is placed on the metabolic plasticity of OCSCs, which can transform between a relatively inactive quiescent state and a highly proliferative active state. This adaptability allows OCSCs to respond dynamically to microenvironmental changes, facilitate ovarian cancer implantation and metastasis, and evade chemotherapeutic stress. We further analyze the molecular networks governing OCSC metabolism, including key signaling cascades and transcription factors. From a therapeutic perspective, we discuss the anti-diabetic drug metformin, which has demonstrated potential in targeting CSC metabolism in both preclinical models and clinical studies. Finally, we outline future research directions aimed at exploiting the metabolic vulnerabilities of OCSCs. We highlight that combination strategies targeting metabolism hold significant potential for overcoming treatment resistance and preventing ovarian cancer recurrence.